Energy-Efficient Permutation Flow Shop Scheduling Problem: A Systematic Literature Review - Utama, Dana Marsetiya; Primayesti, Meri Dines; Umamy, Sabila Zahra; Kholifa, Bunga Milenia Nur (Department Industrial Engineering, University of Muhammadiyah Malang, 2024)
Energy-efficient scheduling is an important problem in the industrial world because improper scheduling can increase energy consumption. One of the production scheduling problems is the Permutation Flow Shop Scheduling Problem (PFSP). This article tries to review research on energy-efficient PFSP to provide a comprehensive review of trends and research gaps in energy-efficient PFSP. A systematic literature review (SLR) was used to conduct this research survey, and 123 articles were collected from 2011-2023. This SLR classifies articles based on publication year, type, objective function, and optimization method used. The results of the literature review analysis show a significant increase every year for energy-efficient PFSP, and multi-objective problems are the dominant problems studied. Based on the analysis of solutions to solve energy efficient PFSP, metaheuristic procedures are the procedures that contribute the largest to solving energy efficient PFSP, and the objective function that is popularly used is to minimize total energy consumption. In addition to this, this study presents a gap research analysis and future research directions for energy-efficient PFSP.